Girl interrupted! The impact of child marriage on women's educational attainment in Zambia - Banda, Mwenzie (School of Economics, 2025)
Human capital acquisition is not only pivotal for overall growth and development, but also plays a critical role in advancing the economic empowerment of women and young girls. However, significant barriers continue to impede girls and women from pursuing further education in developing countries. Among the various factors affecting women's education, child marriage frequently emerges as a significant inhibitor. Despite ongoing efforts to eliminate the practice, it remains prevalent in Sub-Saharan Africa and South Asian countries. Utilising data from the 2018 Demographic and Health Survey (DHS), this dissertation investigates the effects of child marriage on educational outcomes for women in Zambia. Adopting an instrumental variable methodology to account for endogeneity and reverse causality, this paper explores whether marrying below the age of 18 disrupts educational attainment and, consequently, impedes the development of human capital among young Zambian women. Consistent with previous studies on child marriage and education, the results from this paper suggest that being a child bride significantly reduces educational attainment by 1.4 years and reduces the probability of secondary school completion for girls in Zambia by 21 percentage points. In terms of educational attainment, girls married between the age of 10-14 are the most adversely affected.